The Effect of wordwall.net on Students’ Vocabulary Mastery in Reading Narrative Text at SMK Muhammadiyah 2 Pekanbaru - Safitri, Nadya Wahyuni; Aruan, Rumiri; Prawati, Atni (Asatiza: Jurnal Pendidikan, 2024)
This study examined the effect of Wordwall.net has any effect on students’ vocabulary mastery in reading the narrative texts of the tenth-grade students of SMK Muhammadiyah 2 Pekanbaru in 2023/2024. This research used a true experimental design with quantitative approach by randomly selecting the sample. Class 10 Pengembangan Perangkat Lunak dan Gim (PPLG) 1 selected as the experimental class (taught using Wordwall.net) and class 10 Pemasaran as the control class (taught using the conventional method). Data collected using pre-tests and post-tests, then analyzed using SPSS 24. The results revealed that the average pre-test and post-test score in the experimental class was increased by 8.93%, while in the control class, it only increased by 3.49%. The result of the independent sample T-test was 0.048, which is smaller than the alpha value (0.05). Based on the study’s results, it can be concluded that using Wordwall.net influenced students’ vocabulary mastery in reading narrative texts.